Targeting lipoprotein(a) in premature atherosclerotic cardiovascular disease: from pathophysiology to RNA-based therapeutics - a narrative review - Łukasz, Krzysztof; Gwałt, Paweł; Nowakowski, Michał; Marzec, Jakub; Rakuś, Madgalena; Musioł, Aleksandra (Journal of Education, Health and Sport, 2026)
Background. Elevated lipoprotein(a) [Lp(a)] is an independent, genetically determined risk factor for atherosclerotic cardiovascular disease (ASCVD). In young patients presenting with premature atherosclerotic cardiovascular disease (pASCVD), Lp(a) often emerges as the primary driver of residual cardiovascular risk, persisting despite aggressive low-density lipoprotein cholesterol reduction. Aim. This review aims to summarize the pathophysiology of Lp(a) in the context of plaque vulnerability, evaluate the limitations of current lipid-lowering therapies, and analyze emerging pharmacological interventions including new RNA-targeted therapies. Material and methods. A comprehensive search of PubMed-MEDLINE and ClinicalTrials.gov was conducted for articles published in English up to March 2026. Keywords included: lipoprotein(a), Lp(a), Lp(a) lowering, premature ASCVD, siRNA, pelacarsen, and olpasiran. We prioritized randomized controlled trials, meta-analyses, and current societal guidelines. Results. Traditional lipid-lowering agents, including statins, show no significant effect on Lp(a) levels. Conversely, a novel class of RNA-targeted therapeutics - comprising antisense oligonucleotides (pelacarsen) and small interfering RNAs (olpasiran, zerlasiran, lepodisiran) - demonstrates high efficacy in Phase 1 and 2 trials, achieving near-total (up to 98%) and sustained suppression of Lp(a) concentrations. Conclusions: The advent of RNA-based therapies represents a significant therapeutic advance in preventive cardiology, transforming Lp(a) from an unmodifiable risk marker into a therapeutic target. While ongoing Phase 3 cardiovascular outcomes trials predominantly enroll older cohorts, Mendelian randomization studies suggest that early initiation of Lp(a) lowering in the pASCVD population may yield the greatest long-term clinical benefits.